Answer:
(2,4) is a solution to this system of equations
Step-by-step explanation:
Given system of equation are
To find the solution of the given system of equations
To Check that (2,4) is a solution to this system or not
Solving equations (1) and (2)
From equation (1) and y=2x
Now substitute y=2x is equation (2)
10-5x=0
-5x=-10
Substitute x=2 in equation (1)
y=2x
y=2(2)
Therefore y=4
Therefore the solution is (2,4)
Therefore (2,4) is a solution to the system of equations.
Answer:
x-less than-or-equal-to 3
Step-by-step explanation:
4x + 6 < 18 (less than or equal to)
4x < 12 (less than or equal to) x < 3 (less than or equal to)
Let n be a number of friends at the perty. If <span>dinner costs $30 per person, then it cost $30n for all friends.
</span>
Robert has booked a banquet hall which costs <span>$200, then his total expenses are $200+30n.
</span>
If the final bill is p, then p=<span>200+30n.
</span>
Answer: p=<span>200+30n.</span>
Answer:
<h3>
ln (e^2 + 1) - (e+ 1)</h3>
Step-by-step explanation:
Given f(x) = ln and g(x) = e^x + 1 to get f(g(2))-g(f(e)), we need to first find the composite function f(g(x)) and g(f(x)).
For f(g(x));
f(g(x)) = f(e^x + 1)
substitute x for e^x + 1 in f(x)
f(g(x)) = ln (e^x + 1)
f(g(2)) = ln (e^2 + 1)
For g(f(x));
g(f(x)) = g(ln x)
substitute x for ln x in g(x)
g(f(x)) = e^lnx + 1
g(f(x)) = x+1
g(f(e)) = e+1
f(g(2))-g(f(e)) = ln (e^2 + 1) - (e+ 1)